2020
DOI: 10.1002/anie.201914958
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium Boranes for the Selective Transport of Fluoride Anions across Artificial Phospholipid Membranes

Abstract: With the view of developing selective transmembrane anion transporters, a series of phosphonium boranes of general formula [p‐RPh2P(C6H4)BMes2]+ have been synthesized and evaluated. The results demonstrate that variation of the R group appended to the phosphorus atom informs the lipophilicity of these compounds, their Lewis acidity, as well as their transport activity. Anion transport experiments in POPC‐based large unilamellar vesicles show that these main‐group cations are highly selective for the fluoride a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…21 Advances in the eld of hydrogen-bond donor anionophores have inspired parallel efforts based on chloridophilic main group compounds. [22][23][24][25][26][27] Owing to their elevated and welldocumented anion affinity, antimony derivatives have drawn attention. In a recent study, Matile and co-workers showed that SbPh(C 6 F 5 ) 2 is an active chloride anion transporter that interacts with the anion via pnictogen-bonding.…”
Section: Introductionmentioning
confidence: 99%
“…21 Advances in the eld of hydrogen-bond donor anionophores have inspired parallel efforts based on chloridophilic main group compounds. [22][23][24][25][26][27] Owing to their elevated and welldocumented anion affinity, antimony derivatives have drawn attention. In a recent study, Matile and co-workers showed that SbPh(C 6 F 5 ) 2 is an active chloride anion transporter that interacts with the anion via pnictogen-bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the Lewis acidity of the borane unit is readily regulated by the substituents at the P atom and reaches its maximum for compound 13 d (R=Ph), which shows the highest affinity for the fluoride. This efficient complexation of the F − by the borane combined with cell penetrating ability of the phosphonium group has been lately applied for the selective transport of this anion across phospholipid membrane by 13 b and similar compounds [31] …”
Section: Acyclic Organophosphorus Cationic Chromophoresmentioning
confidence: 99%
“…19 On the one hand, the lipid bilayer is a dynamic two-dimensional uid, which renders the cellular membrane with elasticity and exibility. 20 On the other hand, driven by intermolecular forces, bilayerspanning helices are assembled into versatile membrane proteins with N-and C-termini heading towards the cytosol, and these specialized membrane proteins are featured with well-de ned angstrom-scale channels and chemical functionality, 21,22 which synergistically combine size, charge, van der Waals, and other speci c binding interactions to achieve the selective and super-fast transport of target species. 23,24 For example, the AQP within cellular membrane exhibits a high permeability of 3 × 10 9 H 2 O molecules per second per AQP subunit but completely excludes all ionic species; 25 the CO 2 permeability can reach up to 120000 molecules per second per AQP subunit; 26 the potassium permeation rate is ~ 10 8 ions/s with a super high potassium/ sodium ion selectivity of ~ 1000.…”
Section: Introductionmentioning
confidence: 99%